2018
DOI: 10.1021/acsami.8b09988
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Pd@Ru Core–Shell Nanorods for Hydrogen Evolution Reaction in Alkaline Solution

Abstract: The activity and stability of bimetallic nanocatalysts strongly depend on their structures, compositions, and interfaces. Here, we report the synthesis of mesoporous Pd@Ru core-shell bimetallic nanorods composed of face-centered cubic Pd and hexagonal close-packed Ru. The nanorods have two types of cavities with diameters of 3.0 ± 0.9 and 20.3 ± 8.1 nm. The mutual diffusion process between Ru and Pd is characterized by the high-angle annular dark-field scanning transmission electron microscopy, energy-dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 36 publications
0
35
1
Order By: Relevance
“…[19] Although singleatomic Ru catalysts have been provenw ith good catalytic performance, [20,21] it can be further improved througha lloying with other metals or composite strategy. [22,23] Additionally,Prich metal phosphides with highly efficient catalytic properties have attractedw ide interest when comparedw itho ther deficient metal phosphides. [24,25] What is more,t he combination with carbonous material could effectively facilitate the electron transfer and improvet he HER performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] Although singleatomic Ru catalysts have been provenw ith good catalytic performance, [20,21] it can be further improved througha lloying with other metals or composite strategy. [22,23] Additionally,Prich metal phosphides with highly efficient catalytic properties have attractedw ide interest when comparedw itho ther deficient metal phosphides. [24,25] What is more,t he combination with carbonous material could effectively facilitate the electron transfer and improvet he HER performance.…”
Section: Introductionmentioning
confidence: 99%
“…It also achieves similar bond strength with hydrogen (Ru−H) compared to Pt (Pt−H) . Although single‐atomic Ru catalysts have been proven with good catalytic performance, it can be further improved through alloying with other metals or composite strategy . Additionally, P‐rich metal phosphides with highly efficient catalytic properties have attracted wide interest when compared with other deficient metal phosphides .…”
Section: Introductionmentioning
confidence: 99%
“…synthesized Pd@Ru core‐shell nanorod electrocatalysts. [ 98 ] The Pd@Ru core‐shell nanorods have two cavities with diameters of 3.0 ± 0.9 nm and 20.3 ± 8.1 nm, respectively (Figure 6A). In addition, the mesoporous Pd@Ru nanorods exhibited excellent electrocatalytic performance and stability in the HER (the overpotential of was 30 mV at10 mA· cm −2 in 1.0 M KOH solution, and was 37 mV at 10 mA· cm −2 in 0.5 M H 2 SO 4 solution).…”
Section: Npcs and Its Advantagesmentioning
confidence: 99%
“…Reproduced with permission. [ 98 ] Copyright 2018, American Chemical Society. B, TEM images of the NiCo 2.148 O 4 nanocrystals.…”
Section: Npcs and Its Advantagesmentioning
confidence: 99%
“…For example, the kinetics on Pt in alkaline HER is several orders of magnitude lower than that in acidic solutions, but the activity differences for Ru-based electrocatalysts in acidic and alkaline solutions are marginal. [236][237][238] Zheng et al reported an anomalous fcc Ru catalyst fabricated through reduction and annealing treatment. 239 This catalyst showed 2.5 times higher hydrogen generation rate than that of Pt in 0.1 M KOH.…”
Section: Hydrogen Evolution Reaction (Her)mentioning
confidence: 99%